The Molecular Cytogenetic Characterization of Pistachio (Pistacia vera L.) Suggests the Arrest of Recombination in the Largest Heteropycnotic Pair HC1 - Sola-Campoy, Pedro J. (PLoS One, 2015)
This paper represents the first molecular cytogenetic characterization of the strictly dioecious pistachio tree (Pistacia vera L.). The karyotype was characterized by fluorescent in situ hybridization (FISH) with probes for 5S and 45S rDNAs, and the pistachio specific satellite DNAs PIVE-40, and PIVE-180, together with DAPI-staining. PIVE-180 has a monomeric unit of 176–178 bp and high sequence homology between family members; PIVE-40 has a 43 bp consensus monomeric unit, and is most likely arranged in higher order repeats (HORs) of two units. The P. vera genome is highly heterochromatic, and prominent DAPI positive blocks are detected in most chromosomes. Despite the difficulty in classifying chromosomes according to morphology, 10 out of 15 pairs (2n = 30) could be distinguished by their unique banding patterns using a combination of FISH probes. Significantly, the largest pair, designated HC1, is strongly heteropycnotic, shows differential condensation, and has massive enrichment in PIVE-40 repeats. There are two types of HC1 chromosomes (type-I and type-II) with differing PIVE-40 hybridization signal. Only type-I/II heterozygotes and type-I homozygotes individuals were found. We speculate that the differentiation between the two HC1 chromosomes is due to suppression of homologous recombination at meiosis, reinforced by the presence of PIVE-40 HORs and differences in PIVE-40 abundance. This would be compatible with a ZW sex-determination system in the pistachio tree.